Políticas públicas de formação continuada de professores da Educação Básica: impactos no Ensino Fundamental I da Rede Municipal de Uberaba-MG - Nogueira, Adrinelly Lemes (2020)
This research is the result of an investigation developed in the Post-Graduation Program on Education at the Federal University of Uberlândia-MG, at Doctorate level, in the research line “State, Politics and Management in Education” and its central theme is the study of public policies on teacher continuing training of Basic Education teachers focusing on the Elementary Education level I. It aimed to understand how public policies of continuing teacher training of Basic Education teachers, in Brazil, influenced and influence continuing education training policies in the public education network in Uberaba, a municipality in Minas Gerais, as well as its advances, limits and possibilities from 2014 to 2019. The investigation is qualitative in nature and dialectical approach was chosen as epistemological orientation to enable knowledge of reality and its interrelations. Concerning designs, the following modalities were used: bibliographic research, documentary research and field research. As theoretical basis, a dialogue was established mainly with the authors: Libâneo (2016), Kosik (1976), Imbernón (2009) and Freitas (2018). The main documents consulted and/or analyzed were: a) at national level: Education Guidelines and Bases Law (LDB nº 9394/1996); and National Education Plan (PNE 2014/2024); b) at municipal level: Uberaba Municipality Educational Plan (2013-2016); Education Management Plan of the Municipality of Uberaba-MG; Teacher Career Plan and Payment of Uberaba-MG; and the 10-year Education Plan of Uberaba-MG (2015-2024). In this empirical research, online questionnaires were used as data collection, applied to ten teachers with permanent contracts, working in Elementary School I in Uberaba municipality network, and to eight directors from these institutions. The answers were distributed into categories, results were described, inferences were formulated and data were interpreted based on the theoretical framework researched. Regarding the limiting points of public policies built and implemented in Uberaba-MG (2014 to 2019), we highlight: discontinuity of programs; budget cuts; delaying goals; poor use of training time, with significant time dedicated to bureaucratic and administrative issues; and teacher accountability for problems and limits in the quality of education, among others. As positive points or advances arising from public policies from the municipality in relation to continuing education, the following ones should be pointed out: consistent Uberaba municipality policies related to the continuing education of teachers, guided by national public policies; construction of Uberaba Municipality Education Plan, wellgrounded both theoretically and legally; and successful training actions and practices, guided by a plan with rich theoretical foundation, among others. As for possibilities, or perspectives for improving public policies and practices related to the continuing education of Basic Education teachers, especially in Elementary Education I, these ones can be listed: the development of continuing education plans for teachers based on the needs indicated by Elementary School teachers; the assurance of the continuity of training projects, as well as their investments; and the understanding that in addition to training, education professionals must be valued under the conditions of strict obedience of teachers' minimum salary and improvement of working conditions.